HRS-4642 combined with nimotuzumab in the treatment of recurrent or metastatic pancreatic ductal adenocarcinoma: study protocol of a single-arm, prospective phase Ib/II trial - Leng, Qingqing; Zhou, Jitao; Wang, Xin; Zhang, Pei; Xu, Huanji; Cao, Dan (Frontiers in Pharmacology, 2025)
BackgroundPancreatic tumors are highly lethal and a leading cause of cancer mortality. While systemic chemotherapy is the mainstay for advanced disease, its efficacy remains limited. KRAS mutations occur in approximately 88% of pancreatic ductal adenocarcinoma (PDAC), of which KRAS G12D comprises up to 39.5%. Despite the promise of KRAS G12D inhibitors, drug resistance persists. Combining KRAS and EGFR inhibitors has shown clinical efficacy in select solid tumors.ObjectivesTo assess the safety and efficacy of HRS-4642 (KRAS G12D inhibitor) plus nimotuzumab (EGFR inhibitor) in patients harboring the KRAS G12D mutation, recurrent/metastatic PDAC refractory to standard systemic therapy.DesignThis is an open-label, single-center, exploratory clinical trial.MethodsThis study will enroll patients with histologically or cytologically confirmed recurrent or metastatic PDAC harboring the KRAS G12D mutation, who have documented disease progression or intolerance to first-line systemic therapy. In Phase Ib, the safety profile of the investigational agent HRS-4642 will be assessed starting at an initial dose of 1,200 mg administered every 2 weeks (Q2W). Dose reductions to 1,000 mg Q2W or 800 mg Q2W will be implemented for dose-limiting toxicities. The recommended Phase II dose (RP2D) of HRS-4642 in combination with nimotuzumab (400 mg weekly, QW) will be determined based on safety and preliminary efficacy evaluation. Phase II will employ Simon’s two-stage minimax design, with planned enrollment of approximately 20 participants. The primary endpoints for Phase Ib are safety profile characterization and RP2D determination; secondary endpoints include objective response rate (ORR), progression-free survival (PFS), overall survival (OS), disease control rate (DCR), and duration of response (DoR). For Phase II, the primary endpoint is ORR, with secondary endpoints comprising PFS, OS, DCR, safety, and DoR.DiscussionThis exploratory clinical trial may yield critical safety/efficacy data supporting novel combination therapy for advanced PDAC. Its findings could advance the application paradigm of dual-target inhibition in pancreatic cancer therapeutics.Trial registrationThis study was registered on ClinicalTrials.gov with NCT06773130.EthicsThis study protocol has been approved by the Ethics Committee of West China Hospital [2024 (2239)].